A systemic review and meta-analysis on the efficacy and safety of ferumoxytol for anemia in chronic kidney disease patients. Issue 1 (31st December 2022) - Zuo, Qianwei; Wang, Taizhong; Zhu, Lirong; Li, Xiao; Luo, Qi
Abstract: Purpose: To evaluate the efficacy of ferumoxytol, relative to conventional iron supplement formulations, on hemoglobin levels, ferritin level, and adverse event incidence in chronic kidney disease patients. Methods: We performed a systematic search of six academic databases (EMBASE, CENTRAL, Scopus, PubMed, Web of sciences, and MEDLINE), adhering to PRISMA guidelines. We performed a meta-analysis on relevant studies to evaluate the overall influence of ferumoxytol, relative to conventional iron supplement formulations, on hemoglobin levels, ferritin level, and treatment related treatment emergent adverse events (TEAEs) incidence in chronic kidney disease patients. Results: Seven eligible studies were identified from a total of 1397 studies. These studies contained data on 3315 participants with chronic kidney disease (mean age: 59.2 ± 4.6 years). A meta-analysis revealed that ferumoxytol administration had positive effects on hemoglobin levels (Hedge's g statistic: 0.51) and ferritin level (0.88), transferrin saturation (0.39). Besides, we also report reduced incidence of treatment related TEAEs (−0.24) for patients consuming ferumoxytol as compared conventional iron supplement formulations. Conclusions: This meta-analysis provides preliminary evidence that ferumoxytol use exerts beneficial effects on the overall hematological outcomes in patients with chronic kidney disease. This study also reports improved treatment related safety profile for ferumoxytol when compared with conventional iron formulations. The findings from this study can have direct implications in forming best practice guidelines for managing anemia in patients with chronic kidney disease.